A 'Stepped Approach' to Disputes on International Watercourses - Denoon, Riley T. (International Law E-books Online, Collection 2026., 2025)
With increasing global pressure on scarce international water resources, the importance of dispute avoidance and resolution at the international level cannot be understated. A 'Stepped Approach' to Disputes on International Watercourses explores a conceptual and practical framework for addressing these complex challenges, presenting a structured, multi-faceted approach that integrates technical expertise, diplomatic negotiations, and, when necessary, binding adjudication. Drawing on a broad analysis of 225 international watercourse agreements, it puts forward a 'stepped approach' as an important tool that can foster cooperation, prevent conflicts, and ensure the equitable and sustainable use of our shared water resources.